2009
DOI: 10.1038/nchembio.196
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound FRET probe visualizes MMP12 activity in pulmonary inflammation

Abstract: MMP12 is a metalloproteinase implicated in inflammation. To monitor its activity, we synthesized a membrane-targeted reporter (LaRee1) based on Foerster resonance energy transfer (FRET). Unlike existing sensors, LaRee1 detects MMP12 activity by loss of FRET plus internalization of the lipidated fragment. In bronchoalveolar lavages from a mouse model of pulmonary inflammation, LaRee1 detected MMP12 activity at the surface of activated macrophages. LaRee1 may become a powerful tool for monitoring lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 21 publications
2
85
0
5
Order By: Relevance
“…After the elimination of cell content by centrifugation, probe 2 was simply added to the remaining BALf after sample dilution by a factor of two. In a mouse model of lung inflammation, Cobos-Correa et al detected, with a membrane-bound FRET probe, the active form of MMP-12 mostly on the surface of macrophages rather than in BALf (46). Here, with probe 2, active forms of MMP-12 were detected only in BALf.…”
Section: Discussionmentioning
confidence: 93%
“…After the elimination of cell content by centrifugation, probe 2 was simply added to the remaining BALf after sample dilution by a factor of two. In a mouse model of lung inflammation, Cobos-Correa et al detected, with a membrane-bound FRET probe, the active form of MMP-12 mostly on the surface of macrophages rather than in BALf (46). Here, with probe 2, active forms of MMP-12 were detected only in BALf.…”
Section: Discussionmentioning
confidence: 93%
“…In this context, ongoing studies indicate that airway surface dehydration may cause activation of macrophages by particulates or irritants that are not properly cleared from mucostatic airways, causing elevated expression of macrophage elastase (matrix metalloprotease 12), which may be implicated in emphysema formation in bENaC-TG mice [30][31][32]. Notably, besides small airway mucus obstruction, early-onset emphysema has been reported as an early and invariable feature in the lungs of CF infants who died in the first year of life [3], highlighting the clinical importance of this phenotype in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a very elegant study, COBOS-CORREA et al [73] investigated the presence of active MMP-12 in macrophages from BAL from mice exposed to ambient PM10. Using a ratiometric fluorescence resonance energy transfer reporter specific for MMP-12 (LaRee1) that is lipidated and targeted to the plasma membrane, they showed that active MMP-12 was present in the membrane of macrophages of animals instilled with the PM10.…”
Section: Particulate Mattermentioning
confidence: 99%
“…2) MMP-1 mRNA and protein expression can be induced via the MAPK ERK1/2, secondary to the action of NOX4 or b-arrestin (DEP exposure). 3) Active MMP-12 is located in macrophage membranes after exposure to PM10 [73].…”
Section: Mechanisms and Consequences Of Mmp Modulation By Air Pollutantsmentioning
confidence: 99%